Board structure and bank performance: Evidence from Ethiopia - Alem Gebremedhin Berhe (Cogent Business & Management)
This study aims to examine whether board structure (board size, board composition, CEO duality, and board gender diversity) is associated with bank performance. To do so, the study makes use of panel data of 14 commercial banks in Ethiopia covering a 9-year period during 2011–2019 which results in 126 bank-year observations. The findings of the study show that board composition (BCOMP) and board gender diversity (FDIRS) have positive and significant impacts on bank performance. This implies that the increase in the proportion of independent directors and female board members in the board room increases bank performance. On the other hand, the results reveal that board size (BSIZE) and CEO duality (DUAL) decrease bank performance: Both of these variables have significantly negative effects on bank performance. This means that bank performance decreases as the number of board of directors increases. Also, bank performance decreases when a single individual is jointly responsible for the CEO position with the board of directors as well as board chairperson responsibilities. The results suggest that the board has a considerable role in the Ethiopian bank governance. Hence, the results could benefit policy experts and regulators to formulate policies on recuperating board governance.